Rigor Me This: What Are the Basic Criteria for a Rigorous, Transparent, and Reproducible Scientific Study? - Sansbury, Brian E.; Nystoriak, Matthew A.; Uchida, Shizuka; Wysoczynski, Marcin; Moore, Joseph B. (Frontiers in Cardiovascular Medicine, 2022)
Scientific advancement is predicated upon the ability of a novel discovery to be independently reproduced and substantiated by others. Despite this inherent necessity, the research community is awash in published studies that cannot be replicated resulting in widespread confusion within the field and waning trust from the general public. In many cases, irreproducibility is the unavoidable consequence of a study that is conducted without the appropriate degree of rigor, typified by fundamental flaws in approach, design, execution, analysis, interpretation, and reporting. Combatting the irreproducibility pandemic in preclinical research is of urgent concern and is the primary responsibility of individual investigators, however there are important roles to be played by institutions, journals, government entities, and funding agencies as well. Herein, we provide an updated review of established rigor criteria pertaining to both in vitro and in vivo studies compiled from multiple sources across the research enterprise and present a practical checklist as a straightforward reference guide. It is our hope that this review may serve as an approachable resource for early career and experienced investigators alike, as they strive to improve all aspects of their scientific endeavors.